(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2026)
This thesis reviews a pragmatic framework for non-invasive diagnosis in metabolic-related steatohepatitis, focusing on test selection, sequencing, interpretation pitfalls, and pathway implementation across primary care and specialist settings.